Enhancing Low-Light Images: A Synthetic Data Perspective on Practical and Generalizable Solutions - Long, Yu; Lin, Qinghua; Wang, Zhihua; Zhang, Kai; Zhang, Jianguo; Fang, Yuming (Proceedings of the AAAI Conference on Artificial Intelligence, 2025)
Recently, deep neural networks (DNNs) have emerged as the leading approach for low-light image enhancement (LLIE). However, training these models generally requires large-scale paired datasets, which are challenging to obtain due to the labor-intensive and time-consuming nature of real-world data collection. To alleviate this issue, synthetic data are often combined with real-captured data for training. However, most existing low-light image synthesis methods are simply performed in the sRGB domain using Gamma correction or manual adjustments via Lightroom, which fail to incorporate the physical imaging prior through the image signal processing (ISP) pipeline and thus result in limited dataset size and degradation space. Consequently, LLIE methods trained on such data often exhibit some drawbacks in the results, such as inaccurate white balance and abnormal enhancement artifacts, which limit their practicality and generalizability. In this paper, we propose a practical low-light image synthesis pipeline capable of generating unlimited paired training data. Our pipeline starts with a reverse ISP model that converts sRGB images back to the unprocessed RAW domain, where we then simulate low-light degradation, noise degradation, and white balance adjustments. Finally, the degraded RAW images are processed through a forward ISP model to produce low-light sRGB images. The pipeline further employs multiple tone mapping curves and color correction matrices (CCMs) to expand the degradation space. Hence, trained with our proposed synthetic data, existing state-of-the-art (SOTA) LLIE deep models are expected to improve their performance. Extensive experiments across various datasets demonstrate that our synthetic data can indeed effectively enhance existing LLIE deep models, improving both their practicality and generalizability.